Child pornography and the law: Of Good Report (2013). Reopening debates on secrecy, information and censorship. (1st October 2014) - Tomaselli, Keyan
The first cinema-release South African made film to be banned since the fall of apartheid was Of Good Report (2013). This article discusses the broader context of the banning, its unbanning, and the debates that occurred. These are linked to broader issues of freedom of media and democracy, of who gets to decide, and the nature of increasingly repressive state–civil society relations. Issues of censorship, regulation of images and audience agency are examined.